Political Economy of The Procurement of The Changbogo Submarine Alutsista in The Framework of Towards An Independent Process For The Indonesian Defense Industry - susdarwono, endro tri (Jurnal Ilmu Ekonomi Terapan, 2019)
The issue of technology transfer becomes an important note in purchasing independence. In order to achieve independence in the domestic defense industry, the purchase of a defense equipment product must be accompanied by a process of technology transfer through an offset mechanism or the level of achievement of technology transfer from foreign producers into the country. The defense industry policy has a direction towards independence, which is expected in the development of the defense industry stage IV in the period 2025 - 2029. The following line of thought is how the defense industry policies and strategies are developed in the framework of independence. In developing the defense industry's policy formulation and strategy, current conditions, success factors, priority scale and future projections are considered. Through long negotiations, Indonesia finally in December 2011 officially signed a procurement contract for 3 units of Changbogo Class (aka - Nagapasa Class) worth US $ 1.1 billion. The first submarine, KRI Nagapasa 403, was received by the Indonesian Navy in August 2017, and the second ship, KRI Ardadedali 404, was also received by the Indonesian Navy in May 2018. While the third ship, KRI Alugoro 405, is currently under construction at the PT PAL shipyard. The purchase of Changbogo submarines from South Korea is accompanied by a transfer of technology which is hoped that Indonesia will be able to produce submarines on its own in the framework of independence for the defense industry. The government enacted Law Number 16 of 2012 concerning the Defense Industry, which gives obligations to the state for the use of the budget in the weapons and defense sector. The most basic is in article 43 of Law Number 16/2012, including the transfer of technology. Keywords: Changbogo Submarine, Defense Equipment, Defense Industry, Political Economy JEL: F50; P16